Strategi Adam Weishaupt dalam Pembentukan Weisha Organisasi Politik Illuminati Tahun 1776 - Faizal Arifin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Singaperbangsa Karawang, 2018)
his background of this research has emerged from various facts and myths about the Illuminati, after Dan Brawn published the popular novel Da Vinci Code. The Illuminati is a secret society founded in 1776 by Adam Weishaupt. Methods used for this research is historical methods, that consists of heuristics, critics, interpretation and historiography, because the aspects of the study are past and related to various archives or old documents. The main problem of this research is to conduct a historical study of the founding of the Illuminati by Weishaupt from the historical perspective. This research presents a brief biography of Adam Weishaupt who was a German academic that influenced by the thoughts of the Age of Enlightenment. Weishaupt had a vision of replacing the government and power of the Catholic Church with a new government. To accomplish this political mission, Weishaupt formed a secret society by recruiting elite groups and intellectuals as members, reaching up to 2,000-3,000 people. In line with this mission, the Illuminati were supported by Protestant princes, Reformed (Lutherans and Calvinists), German and European nobles. Financially, Weishaupt was supported by the family of the banking millionaire, Rothschild. Weishaupt also adopted the Freemasonry system into the Illuminati in terms of secrecy, concealment, membership levels and other matters. Weishaupt's political goal orientation made him also learned from the Jesuits about organizing political missions. Weishaupt and Illuminati should be suspected of having an urgent role in the occurrence of the great events of the French Revolution.Kata kunci : Illuminati, Pencerahan, Freemasonry, Yahudi, Okultisme.